Use of thermography as a training marker and prevention of injuries in sports: a systematic review in volleyball (Research, Society and Development, 2022)
The study aimed to map the scientific productions about the use of thermography as a marker of training and injury prevention in sports, emphasizing volleyball and starting from the following problem: Can thermography be considered as a training marker and as a tool for injury prevention in the most diverse sports? This is a systematic review study and studies were selected from the following databases: LILACS (Latin American and Caribbean Literature on Health Sciences), PUBMED, SCIELO (Scientific Electronic Library Online), CAPES Journal portal and BDTD (Brazilian Digital Library of Theses and Dissertations). The results indicate that there is a low production of studies whose theme is directed to volleyball and that thermography has been increasingly used in a unique way and combined with other methods as a way to prevent and treat injuries in sports.